Al-Ti-CNTs-Re intermediate alloy refiner
By using Al-Ti-CNTs-Re intermediate alloy refining agent, the problem of strength attenuation of aluminum alloy at high temperatures is solved, and the grain refinement and high-temperature performance are significantly improved, which is suitable for the manufacture of high-performance aluminum alloy materials.
Patent Information
- Application Number
- CN202411584873.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-07
AI Technical Summary
The strength attenuation of existing aluminum alloys under high temperature conditions is severe, which is difficult to meet the current performance requirements. Moreover, conventional intermediate alloys fail to significantly improve high-temperature performance while refining grains.
Using Al-Ti-CNTs-Re intermediate alloy refiner, Al powder, TiC powder, CNTs powder and Re powder are mixed in a specific proportion, ball milled, cold pressed, and self-propagation reaction is carried out in a vacuum environment to generate self-propagation reaction After the spread product, add it to the aluminum liquid, dilute it to the appropriate Ti element content, and perform casting preparation.
The grain size of aluminum alloy is significantly refined, and its comprehensive mechanical properties are improved, especially the tensile strength at high temperatures, which reduces the tendency of grain growth and agglomeration, and improves the high-temperature performance and stability of aluminum alloys.
Smart Images

Figure CN119392032A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonferrous metal smelting, and relates to a grain refiner, in particular to an intermediate alloy refiner used for grain refinement of aluminum alloy. Background Art
[0002] The modernization process of industrialization is constantly improving, science and technology, especially high-end science and technology, are developing rapidly, and the comprehensive performance requirements of various materials are increasing. Aluminum alloy materials are usually composed of aluminum and other metal elements such as copper, magnesium, zinc, manganese, silicon, etc. They have the advantages of light weight, high strength, corrosion resistance, high thermal conductivity, easy processing, and easy forming. As an important engineering material, they have been widely used in various fields.
[0003] Among them, Al-Cu-Mn alloy is often used as a precision casting material for use under high temperature conditions due to its advantages such as high strength, light weight, good toughness, large modulus, and fast production and preparation. It has been widely used in the fields of automobiles, aerospace, ships, and military industries. Although Al-Cu-Mn alloy has excellent mechanical properties, under high temperature conditions, due to grain boundary softening and grain ripening, its alloy performance will drop significantly compared to room temperature performance, and its strength will decrease. Therefore, improving the high temperature performance of the alloy is the key to broadening the application range of Al-Cu-Mn alloy.
[0004] Grain refinement is one of the important ways to improve the comprehensive mechanical properties of materials. However, the current mainstream refinement methods have the following problems:
[0005] 1. The grain size can be reduced by lowering the casting temperature and accelerating the cooling of the melt, but at the same time the fluidity of the melt is greatly reduced, the alloy fluidity is poor, and the casting is prone to defects such as insufficient pouring and cold shut during the production process. The casting will also produce dispersed shrinkage, pores, slag inclusions and other defects inside, which will reduce the quality of the casting and affect the performance and air tightness of the casting.
[0006] 2. Kotadia et al. can significantly refine the grain size of aluminum alloy castings by applying physical external fields such as ultrasound and electromagnetics during the solidification process. Many studies have shown that power ultrasound can promote activation, degassing, filtration, non-dendritic solidification and semi-solid deformation, and electromagnetic fields can reduce macro-segregation and obtain ingots with uniform structure and fine grains. However, these methods and equipment consume a lot of energy and have high requirements for the stability of casting equipment. When the ingot specifications are too large, the magnetic field has a limited penetration depth into the melt, and the electromagnetic stirring effect will be weakened accordingly. The different states of the internal and external melts also lead to uneven performance, making it difficult to be widely used.
[0007] Adding a small amount of intermediate alloy with nucleation ability into the aluminum melt can also achieve the effect of grain refinement, and it is the most convenient method.
[0008] In the 1960s, foreign research found that Al-Ti-B master alloy has good refining effect. However, with its wide application in the industrial field, people found that the TiB2 particles contained in the Al-Ti-B master alloy would react when facing alloy elements such as zirconium and silicon, resulting in a large number of heterogeneous nucleation particles being consumed and the refining effect being weakened, which is the "poisoning" phenomenon.
[0009] Based on the shortcomings of Al-Ti-B master alloy, Banerji et al. used graphite to replace B to prepare Al-Ti-C master alloy, which solved the problem of "poisoning" and had the same refining ability as Al-Ti-B master alloy. However, the wettability of graphite and Al is insufficient, not only the reaction is not thorough, the remaining C residue pollutes the melt, and the contained TiC is large in size and easy to settle, and the refining ability is greatly reduced under long holding time.
[0010] In 2018, Jiang et al. replaced the common carbon source with CNTs to generate a new Al-Ti-CNTs master alloy. Due to the unique structure of CNTs, the wettability of carbon source and aluminum melt is greatly improved, the carbon source utilization rate is far higher than that of ordinary carbon source, and the size of TiC contained is greatly reduced to submicron scale. However, its refinement ability is only slightly improved compared with Al-Ti-C, and there is no significant breakthrough.
[0011] With the continuous increase in engine power, higher standards of high temperature resistance are also required for materials used to manufacture engine blocks, cylinder heads, etc. The current commercial aluminum alloys suffer from severe strength degradation under high temperature conditions and are difficult to meet current performance requirements. Conventional master alloys improve the room temperature mechanical properties of aluminum alloys while refining the grains, but do not significantly improve the significant decline in strength at high temperatures.
[0012] Therefore, although the refining effect of refiners has long been confirmed, their strengthening properties, especially the insufficient strengthening effect under high temperature conditions, are the key constraints on high temperature resistant alloys. The development of an intermediate alloy that takes into account both grain refinement and improved high temperature performance is crucial for the engine industry manufacturing field. Summary of the invention
[0013] The purpose of the present invention is to provide a novel Al-Ti-CNTs-Re master alloy refiner, which can refine grains and significantly improve the comprehensive mechanical properties of aluminum alloys, especially high-temperature mechanical properties.
[0014] The Al-Ti-CNTs-Re master alloy refiner of the present invention is prepared by mixing and pressing 30-40wt% of Al powder, 35-40wt% of TiC powder, 10-15wt% of CNTs powder and 10-20wt% of Re powder, and performing high-temperature self-propagating combustion to obtain a self-propagating product. The self-propagating product is then added into molten aluminum liquid, diluted to a Ti element content of 3-10wt% of the total mass, and then cast to obtain a master alloy.
[0015] The present invention also provides a method for preparing a suitable Al-Ti-CNTs-Re master alloy refiner, which specifically comprises:
[0016] 1) Mix the raw materials in a ratio of 30-40wt% of Al powder, 35-40wt% of TiC powder, 10-15wt% of CNTs powder and 10-20wt% of Re powder, and mill the mixture in a vacuum ball mill to obtain alloy powder;
[0017] 2) cold pressing the alloy powder into a shape, and performing a self-propagating reaction in a vacuum environment at 1000-1300° C. to obtain a self-propagating product;
[0018] 3) Add the self-propagating product into the molten aluminum liquid until the Ti content in the aluminum liquid is 3-10wt%, and then smelt evenly and cast to prepare Al-Ti-CNTs-Re master alloy refiner ingot.
[0019] In the preparation method of the Al-Ti-CNTs-Re master alloy refiner of the present invention, the raw materials Al powder and Ti powder preferably have a particle size of no more than 300 μm, and the particle size of CNTs powder and Re powder is no more than 50 nm.
[0020] Furthermore, the raw materials of the present invention should be dried at 100-120°C.
[0021] More specifically, the present invention preferably mixes the mixed raw materials by ball milling at a rotation speed of 200 to 300 rpm for 4 to 6 hours under vacuum conditions.
[0022] Furthermore, the present invention performs cold pressing on the alloy powder at a load of 20 to 25 kN. More preferably, the cold pressing time is 15 to 20 s.
[0023] Preferably, the present invention adds the self-propagating product into the molten aluminum liquid, maintains 950-1000° C. for smelting, and stirs for 15-30 seconds every 5-15 minutes during the smelting process until the self-propagating product is completely melted.
[0024] More preferably, the present invention is to prepare the Al-Ti-CNTs-Re master alloy refiner by pouring the smelted aluminum liquid at high temperature into a metal mold preheated to 200-300°C.
[0025] The diameter of TiC particles generated by the Al-Ti-Cnts master alloy using CNTs as the carbon source is smaller than that of the Al-Ti-C master alloy using graphite as the carbon source, and is basically in the form of nanoparticles with a more dispersed distribution. The present invention realizes the modification of the melt by combining rare earth Re powder with the Al-Ti-CNTs master alloy refiner, improves the wettability between Al powder and CNTs powder, promotes the reaction synthesis of TiC, prevents the growth of the generated grains, refines the alloy structure, further reduces the TiC diameter and reduces the agglomeration tendency.
[0026] The rare earth elements added in the present invention can also have a refining and purifying effect on the melt, remove the hydrogen and oxygen elements in the melt to a great extent, and greatly reduce the true pores and bubbles of the aluminum alloy.
[0027] The Al-Ti-CNTs-Re master alloy refiner of the invention has a simple preparation method, low production cost and high purity of the prepared product.
[0028] The Al-Ti-CNTs-Re master alloy refiner of the present invention can be used as a grain refiner and applied to the preparation of various cast aluminum alloys, forged aluminum alloys or rolled aluminum alloys, and is particularly suitable for the preparation of Al-Cu-Mn alloys.
[0029] The method for using the Al-Ti-CNTs-Re master alloy refiner of the present invention as a grain refiner is simple, and the master alloy only needs to be directly added into the refined aluminum alloy melt.
[0030] Generally, the addition ratio of the Al-Ti-CNTs-Re master alloy refiner in the present invention to the aluminum alloy is preferably 0.1-1 wt %. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the as-cast grain diagram of pure aluminum castings after being refined with different master alloy refiners.
[0032] Figure 2 The following is the as-cast structure diagram of Al-Cu-Mn alloy castings after being refined with different master alloy refiners.
[0033] Figure 3 It is the average grain size of Al-Cu-Mn alloy after being refined with different master alloy refiners.
[0034] Figure 4 This is a trend chart of the high temperature tensile strength performance of ZL205A alloy after being refined with different master alloy refiners.
[0035] Figure 5This is a trend chart of the high temperature tensile strength attenuation of ZL205A alloy refined with different master alloy refiners. Implementation
[0036] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0037] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and unambiguous in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0038] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.
[0039] In the raw materials used in the following examples of the present invention, the fineness of aluminum powder and titanium powder is 300 μm, and the fineness of CNTs powder (or graphite powder) and rhenium powder is 50 nm. Example
[0040] Example 1
[0041] Weigh 40 g of aluminum powder, 40 g of titanium powder, 10 g of CNTs powder and 10 g of rhenium powder, mix and place in an oven, dry at 120°C for 2 h, take out and place in a dry ball mill, evacuate, and ball mill at 200 rpm for 4 h to obtain alloy powder.
[0042] The ball-milled alloy powder was taken out and placed in a cold press mold. A prefabricated block was prepared with a pressure of 20 kN. The prefabricated block was sent into a vacuum sintering furnace and heated to 1100°C for a self-propagating reaction. After the reaction was completed, the self-propagating product was cooled to room temperature in a vacuum environment with the furnace.
[0043] 700g of pure aluminum was weighed and melted at 950℃ to obtain aluminum liquid. The self-propagating product was crushed by a cold press with a pressure of 1t, added to the molten aluminum liquid, mechanically stirred for 30s every 10min until it was completely dissolved, and cast into a metal mold preheated to 200℃, cooled naturally, and Al-Ti-CNTs-Re master alloy refiner ingot was prepared.
[0044] Comparative Example 1
[0045] Weigh 40 g of aluminum powder, 40 g of titanium powder and 10 g of CNTs powder, mix them and place them in an oven, dry them at 120°C for 2 h, take them out and place them in a dry ball mill, evacuate them, and ball mill them at 200 rpm for 4 h to obtain alloy powder.
[0046] The ball-milled alloy powder was taken out and placed in a cold press mold. A prefabricated block was prepared with a pressure of 20 kN. The prefabricated block was sent into a vacuum sintering furnace and heated to 1100°C for a self-propagating reaction. After the reaction was completed, the self-propagating product was cooled to room temperature in a vacuum environment with the furnace.
[0047] 710g of pure aluminum was weighed and melted at 950℃ to obtain aluminum liquid. The self-propagating product was crushed by a cold press with a pressure of 1t, added to the molten aluminum liquid, mechanically stirred for 30s every 10min until it was completely dissolved, and cast into a metal mold preheated to 200℃, cooled naturally, and Al-Ti-CNTs master alloy refiner ingot was prepared.
[0048] Comparative Example 2
[0049] Weigh 40 g of aluminum powder, 40 g of titanium powder and 10 g of graphite powder, mix and place in an oven, dry at 120° C. for 2 h, take out and place in a dry ball mill, evacuate, and ball mill at 200 rpm for 4 h to obtain alloy powder.
[0050] The ball-milled alloy powder was taken out and placed in a cold press mold. A prefabricated block was prepared with a pressure of 20 kN. The prefabricated block was sent into a vacuum sintering furnace and heated to 1100°C for a self-propagating reaction. After the reaction was completed, the self-propagating product was cooled to room temperature in a vacuum environment with the furnace.
[0051] 710g of pure aluminum was weighed and melted at 950℃ to obtain aluminum liquid. The self-propagating product was crushed by a cold press with a pressure of 1t, added to the molten aluminum liquid, mechanically stirred for 30s every 10min until it was completely dissolved, cast into a metal mold preheated to 200℃, and cooled naturally to prepare an Al-Ti-C master alloy refiner ingot.
[0052] Application Example 1
[0053] 1 kg of pure aluminum was weighed, and 20 g of the intermediate alloy refiners prepared in Example 1, Comparative Example 1 and Comparative Example 2 were added respectively to carry out refinement effect experiments, and blank pure aluminum without any refiner was used as a control.
[0054] Pure aluminum is smelted at 730°C, and after melting, an intermediate alloy refiner or no refiner is added, and after mechanical stirring for 2 minutes, hexachloroethane is used for degassing. After the melt temperature drops to 710°C, it is cast into a preheated serpentine mold to obtain a casting.
[0055] Figure 1The as-cast grain diagrams of the castings after the above-mentioned different treatments are given. Among them, the grains of blank pure aluminum are coarse columnar crystals, which are nucleated from the wall end and continue to grow inward, and the grains are coarse. With the addition of the Al-Ti-C intermediate alloy in Comparative Example 2, the grain size is greatly reduced, and equiaxed crystals begin to appear in some grains, but most of them are still slender columnar crystals, and the columnar crystals are significantly refined compared to pure aluminum; the basic distribution is that the center is mostly equiaxed crystals, and the outside is mostly columnar crystals, and the grain size distribution is extremely uneven. After adding the Al-Ti-CNTs intermediate alloy to Comparative Example 1, the equiaxed crystals increase in number while the grain size is also reduced, and the size of the external columnar crystals is also reduced, especially reflected in the length of the external centripetal part; at the same time, the uniformity of its grain size is also improved.
[0056] It can be seen from this that the addition of the intermediate alloy can significantly refine the grains compared to the blank control, and realize the transformation of the grains from columnar crystals to equiaxed crystals. At the same time, the intermediate alloy with CNTs as the carbon source has a better refining effect than graphite, with finer grains and more equiaxed crystals.
[0057] After adding Al-Ti-CNTs-Re master alloy in Example 1, the grain refining ability is further improved. Not only the number of grains increases synchronously, the grain size is further reduced, and the columnar crystals basically disappear and turn into equiaxed crystals, which has the best refining effect.
[0058] Application Example 2
[0059] Al-Cu-Mn alloy was prepared with Cu content of 5wt%, Mn content of 0.8wt% and balance Al.
[0060] When the temperature of the smelting furnace rises to 780°C, put in 2kg of Al-Cu-Mn alloy. After melting, use a stone mill to mechanically stir until it is uniform. Add 10g of intermediate alloy refiner and continue stirring. After 2 minutes, use hexachloroethane for degassing and complete the casting after the temperature drops to 710°C.
[0061] Figure 2 The cast microstructures of Al-Cu-Mn alloys prepared without adding (a) and with adding the intermediate alloy refiners of Comparative Example 1 (b), Comparative Example 2 (c) and Example 1 (d) are given. Figure 3 The corresponding average grain size statistics are further given.
[0062] Among them, (a) the Al-Cu-Mn alloy without intermediate alloy refinement is composed of uneven grains with an average diameter of 420μm; (b) after adding Al-Ti-C intermediate alloy, the grain size is significantly refined, sharply reduced to 79.3μm, and the refinement rate is 81%, but the grain size distribution is uneven, and there is a state of mixed large and small grains; (c) after adding Al-Ti-CNTs intermediate alloy, the grain size is further reduced to 66.7μm, the refinement rate is 84.1%, and the size distribution is relatively uniform; (d) after replacing the intermediate alloy with Al-Ti-CNTs-Re, the refinement effect is best, the grain size is 49.3μm, and the refinement rate is 88.3%. At this time, most of the grains are nearly spherical and the distribution is relatively uniform.
[0063] Application Example 3
[0064] The ZL205A alloy was prepared according to Table 1.
[0065]
[0066] When the temperature of the smelting furnace rises to 780°C, put in 2kg of ZL205A alloy. After melting, use a stone mill to mechanically stir until uniform. Add 10g of intermediate alloy refiner and continue to stir evenly. After 2 minutes, use hexachloroethane for degassing. After the temperature drops to 710°C, complete casting to obtain a Y-shaped metal alloy block.
[0067] According to GB / T 228.2-2015 “Tensile tests on metallic materials - Part 2: High temperature test methods”, samples were taken from the Y-block for high temperature tensile strength test. Each sample was tested 3 times and the average value was taken.
[0068] Table 2 shows the tensile strength results of blank ZL205A alloy without adding refiner and alloy samples after adding Al-Ti-C, Al-Ti-CNTs and Al-Ti-CNTs-Re master alloys at different temperatures.
[0069]
[0070] Figure 4 Further, according to the results in Table 2, the tensile strength variation trends of the above samples at different temperatures were plotted. It can be seen from the figure that compared with the blank ZL205A alloy, after adding Al-Ti-C, Al-Ti-CNTs and Al-Ti-CNTs-Re master alloys, the room temperature and high temperature tensile strengths of the ZL205A alloy were gradually improved, and the Al-Ti-CNTs-Re master alloy had the best performance improvement effect.
[0071] However, as the ambient temperature continues to rise, the tensile strength of ZL205A alloys with different refinement treatments will inevitably decrease gradually. Figure 5 The attenuation trend of the tensile strength of the ZL205A alloy treated with different intermediate alloy refiners as the temperature increases is given. At 100°C, the tensile strengths of the ZL205A alloys with different intermediate alloy refiners were 435, 439 and 460.3 MPa, respectively. The tensile strength gradually increased and the decay gradually decreased. Under the extreme 300°C environment, the tensile strength of the blank ZL205A alloy was reduced to only 144 MPa, while after adding different intermediate alloy refiners, it reached 164, 170 and 225 MPa, respectively, which was increased to 65.8%, 65.7% and 52.9% respectively compared to the decay rate of 69.2% of the blank ZL205A alloy. Combined with Figure 5 It can be seen that the decay amount of Al-Ti-CNTs-Re master alloy is significantly smaller than that of other master alloys. It can be seen that Al-Ti-CNTs-Re has the best high-temperature performance strengthening effect and has stronger anti-decay ability than Al-Ti-C and Al-Ti-CNTs master alloys.
[0072] Example 2
[0073] Weigh 35 g of aluminum powder, 35 g of titanium powder, 15 g of CNTs powder and 15 g of rhenium powder, mix them and place them in an oven, dry them at 100°C for 4 h, take them out and place them in a dry ball mill, evacuate them, and ball mill them at 300 rpm for 6 h to obtain alloy powder.
[0074] The ball-milled alloy powder was taken out and placed in a cold press mold. A prefabricated block was prepared at a pressure of 25 kN. The prefabricated block was sent to a vacuum sintering furnace and heated to 1200°C for a self-propagating reaction. After the reaction was completed, the self-propagating product was cooled to room temperature in a vacuum environment with the furnace.
[0075] 700g of pure aluminum was weighed and melted at 1000℃ to obtain aluminum liquid. The self-propagating product was crushed by a cold press with a pressure of 1t, added to the molten aluminum liquid, mechanically stirred for 20s every 5min until it was completely dissolved, cast into a metal mold preheated to 250℃, and cooled naturally to prepare an Al-Ti-CNTs-Re master alloy refiner ingot.
[0076] Example 3
[0077] Weigh 30 g of aluminum powder, 40 g of titanium powder, 10 g of CNTs powder and 20 g of rhenium powder, mix them and place them in an oven, dry them at 120°C for 2 h, take them out and put them in a dry ball mill, evacuate them, and ball mill them at 300 rpm for 4 h to obtain alloy powder.
[0078] The ball-milled alloy powder was taken out and placed in a cold press mold. A prefabricated block was prepared at a pressure of 25 kN. The prefabricated block was sent to a vacuum sintering furnace and heated to 1000°C for a self-propagating reaction. After the reaction was completed, the self-propagating product was cooled to room temperature in a vacuum environment with the furnace.
[0079] 700g pure aluminum was weighed and melted at 980℃ to obtain aluminum liquid. The self-propagating product was crushed by a cold press with a pressure of 1t, added to the molten aluminum liquid, mechanically stirred for 30s every 5min until it was completely dissolved, and cast into a metal mold preheated to 300℃, cooled naturally, and Al-Ti-CNTs-Re master alloy refiner ingot was prepared.
[0080] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. An Al-Ti-CNTs-Re master alloy refiner is prepared by mixing and pressing 30-40wt% of Al powder, 35-40wt% of TiC powder, 10-15wt% of CNTs powder and 10-20wt% of Re powder, and performing high-temperature self-propagating combustion to obtain a self-propagating product, which is then added to molten aluminum liquid and diluted to a Ti element content of 3-10wt% of the total mass, and then cast to obtain a master alloy.
2. A method for preparing an Al-Ti-CNTs-Re master alloy refiner, comprising: 1) Mix the raw materials in a ratio of 30-40wt% of Al powder, 35-40wt% of TiC powder, 10-15wt% of CNTs powder and 10-20wt% of Re powder, and mill the mixture in a vacuum ball mill to obtain alloy powder; 2) cold pressing the alloy powder into a shape, and performing a self-propagating reaction in a vacuum environment at 1000-1300° C. to obtain a self-propagating product; 3) Add the self-propagating product into the molten aluminum liquid until the Ti content in the aluminum liquid is 3-10wt%, and then smelt evenly and cast to prepare Al-Ti-CNTs-Re master alloy refiner ingot.
3. The preparation method according to claim 2, characterized in that The particle sizes of Al powder and Ti powder are not larger than 300 μm, and the particle sizes of CNTs powder and Re powder are not larger than 50 nm.
4. The preparation method according to claim 2, characterized in that The method also includes drying the raw materials at 100-120°C.
5. The preparation method according to claim 2, characterized in that The mixed raw materials were ball-milled at a rotation speed of 200-300 rpm for 4-6 hours under vacuum conditions.
6. The preparation method according to claim 2, characterized in that The alloy powder is cold pressed at a load of 20 to 25 kN for 15 to 20 seconds.
7. The preparation method according to claim 2, characterized in that The self-propagating product is added to the molten aluminum liquid and smelted at 950-1000°C. During the smelting process, stirring is performed for 15-30 seconds every 5-15 minutes.
8. The preparation method according to claim 2, characterized in that The smelted aluminum liquid is poured into a mold preheated to 200-300° C. to prepare an Al-Ti-CNTs-Re intermediate alloy refiner.
9. Use of the Al-Ti-CNTs-Re master alloy refiner according to claim 1 as a refiner in the preparation of Al-Cu-Mn alloy.
10. The use according to claim 9, wherein 0.1-1 wt% of Al-Ti-CNTs-Re master alloy refiner is added to the Al-Cu-Mn alloy.